Analisis Teks Satua Pan Angklung Gadang: Kajian Amanat - Widasari, Ni Luh Putu Dina; Mulyawati, Tjok Istri Agung (Humanis; Vol 25 No 1 (2021), 2021)
This research is entitled “Amanat Teks Satua Pan Angklung Gadang : Suatu Pendekatan Moral”. This research has function to describe the structure and analyze the instruction appeared on the Teks Satua Pan Angklung Gadang. Data equipping stage used collect-method with record and translate techniques. Data analyze stage used qualitative method. In this stage, the research is supported also with analytical descriptive technique. The method which is used in presentation of data analyzed result is informal method which is supported by deductive and inductive techniques.The result of this research has been showing: there are six analyzed structure which is build Teks Satua Pan Angklung Gadang . They are incident, plot, characters, characterization, setting, theme, and the instruction was analyzed on the different sub-chapter. The plot of Teks Satua Pan Angklung Gadang consist of three plots and all of them are straight plot. Characterization of it describe by the main character from sociological, psychological, and physiological, aspects with setting of the place, time, and atmosphere, along with social criticism as the theme, the instruction which is contained in Teks Satua Pan Angklung Gadang are moral value of honestly, loyality, karmaphala , leadership, ingenuity, and responsibility.